Please help ASAP!I'll give 50 points to whoever gives me the correct answer. And brainliest!1) Explain and/or describe each translation from y=x^2y = x 2 to y=-6\left(x+4\right)^2-7y = βˆ’ 6 ( x + 4 ) 2 βˆ’ 7 (there are 4).2) Explain why 8x^4 - 3x^2 + 3 is even, odd, or neither (Hint: Use Symmetry or f(-x)=f(x)).

Accepted Solution

Answer: Β  1) vertical expansion by a factor of 6, reflection over the x-axis, translation left 4 units, translation down 7 units. Β  2) all terms are of even degree: f(-x) = f(x)Step-by-step explanation:1) The leading minus sign means the function has been reflected over the x-axis. The leading coefficient of magnitude 6 is the vertical expansion factor. The 4 added to x is the number of units of left translation. The 7 subtracted from the previous expression is the number of units of translation downward.The transformations are ...reflection over the x-axisvertical expansion by a factor of 6horizontal translation left 4 unitsvertical translation down 7 units__2) A function f(x) is even if it satisfies f(-x) = f(x). Since all x-terms in the given function are of even degree, we know this will be true: Β  f(-x) = 8(-x)^4 -3(-x)^2 +3 = 8x^4 -3x^2 +3 = f(x)f(x) is even because f(-x) = f(x) indicating it is symmetrical about x=0.